Hope in the uncertainties and certainty for parents of children with rare neurological disorders: Part 2 (of 3): Certainty. (7th September 2022) - Nevin, Suzanne M; Beavis, Erin; Macintosh, Rebecca; Palmer, Elizabeth E; Sachdev, Rani; Le Marne, Fleur A; Bye, Ann ME; Nunn, Kenneth
Abstract : This is the second of a three‐part series that explores different aspects of uncertainty, certainty and hope in the context of providing clinical care for children with rare and life‐limiting neurological disorders. When caring for families impacted by an overwhelming complex disorder in a child, complicated by threatening uncertainties and potentially more threatening certainties, clinicians utilise skills drawn from differing fields to make the load of information, and the emotional impact more manageable. The first article in this series addressed how clinicians might manage the ' accumulation of uncertainties ' and to provide compassionate care not only to their patients, and their families, but also to themselves. This second paper delves into the less helpful aspects of ' certainty ', including the associated losses and griefs endured by parents responding to threatening fears associated with their child's condition. In the extreme, disconnection and psychological isolation borne by parents can lead to a sense of hopelessness and desperation. Facing unwelcome certainties – clinicians and parents together – forms the basis of future trust and hope. Clinicians who share the field of trust with families and show commitment to helping parents, even when cure remains elusive, build a sense of hope. This is the sort of hopefulness that clinicians need to have and to offer as they share the journey with families. In this series, we seek to harness a shared approach to face unwelcome certainties and to kindle a sense of hope that is both credible and meaningful to the parents, family and clinician.